2011
DOI: 10.1111/j.1399-5448.2010.00735.x
|View full text |Cite
|
Sign up to set email alerts
|

Blood glucose monitoring and glycemic control in adolescents with type 1 diabetes: meter downloads versus self-report

Abstract: Meter downloads have the most robust association with glycemic control when contextual variables are considered. Caregiver-reported BGM frequencies can serve as reliable substitutes in the absence of meter download, but they may not be as reliable in adolescents with depressive symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 30 publications
1
49
0
Order By: Relevance
“…There are six reporting on various stages of a longitudinal study involving two sites. Three of the studies (Guilfoyle, Crimmins, & Hood, 2011;McGrady, Peugh, & Hood, 2014; report data from one location and the others report results from both locations (McGrady, Laffel, Drotar, Repaske, & Hood, 2009;Herzer, Vesco, Ingerski, Dolan, & Hood, 2010;Sander, Odell, & Hood, 2010). For the purposes of this review, these will be considered as one study, referred to as the Depression & Diabetes study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are six reporting on various stages of a longitudinal study involving two sites. Three of the studies (Guilfoyle, Crimmins, & Hood, 2011;McGrady, Peugh, & Hood, 2014; report data from one location and the others report results from both locations (McGrady, Laffel, Drotar, Repaske, & Hood, 2009;Herzer, Vesco, Ingerski, Dolan, & Hood, 2010;Sander, Odell, & Hood, 2010). For the purposes of this review, these will be considered as one study, referred to as the Depression & Diabetes study.…”
Section: Resultsmentioning
confidence: 99%
“…Data from the Depression & Diabetes study found a small, negative relationship between depressive symptoms and frequency of BGM (average correlation = .21) (Herzer et al, 2011;Wu et al, 2013), and in regression analyses, adolescents reporting more depressive symptoms reported less frequent BGM (McGrady et al, 2009;Guilfoyle et al; 2011).…”
Section: Emotional Variablesmentioning
confidence: 99%
“…3,4 Adolescents with type 1 diabetes demonstrate poorer adherence to treatment regimens compared to other age-groups, and there are limited data on specific methods to improve adherence among adolescents. 5,6 Driving is one of the most anticipated privileges for many adolescents.…”
Section: License To Drive: Type 1 Diabetes Management and Obtaining Amentioning
confidence: 99%
“…55,61 Despite this lack of consensus on how to best assess BGM, BGM is still often utilized as an indicator of a patient's overall adherence to one's diabetes-specific medical regimen.…”
Section: -60mentioning
confidence: 99%